Hydrocarbon removal and bacterial community structure in on-site biostimulated biopile systems designed for bioremediation of diesel-contaminated Antarctic soil - Dias, Romina Laura; Ruberto, Lucas Adolfo Mauro; Calabró López, Roberto Ariel; Lo Balbo, Alfredo; del Panno, Maria Teresa; Mac Cormack, Walter Patricio (Polar Biology)
Several studies have shown that biostimulation can promote hydrocarbon bioremediation processes in Antarctic soils. However, the effect of the different nutrient sources on hydrocarbon removal heavily depends on the nutrients used and the soil characteristics. In this work, using a sample of chronically contaminated Antarctic soil that was exposed to a fresh hydrocarbon contamination, we analyzed how a complex organic nutrient source such as fish meal (FM) and a commercial fertilizer (OSEII) can affect hydrocarbon biodegradation and bacterial community composition. Both amended and unamended (control) biopiles were constructed and controlled at Carlini Station and sampled at days 0, 5, 16, 30 and 50 for microbiological, chemical and molecular analyses. FM caused a fast increase in both total heterotrophic and hydrocarbon degrading bacterial counts. These high values were maintained until the end of the assay, when statistically significant total hydrocarbon removal (71 %) was detected when compared with a control system. The FM biopile evidenced the dominance of members of the phylum Proteobacteria and a clear shift in bacterial structure at the final stage of the assay, when an increase of Actinobacteria was observed. The biopile containing the commercial fertilizer evidenced a hydrocarbon removal activity that was not statistically significant when compared with the untreated system and exhibited a bacterial community that differed from those observed in the unamended and FM-amended biopiles. In summary, biostimulation using FM in biopiles significantly enhanced the natural hydrocarbon-degradation activity of the Carlini station soils in biopile systems and caused significant changes in the bacterial community structure. The results will be considered for the future design of soil bioremediation protocols for Carlini Station and could also be taken into account to deal with diesel-contaminated soils from other cold-climate areas. Fil: Dias, Romina Laura. Consejo Nacional de Investigaciones Científicas y ...